(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses algorithms for grammatical analysis of Uzbek words, description of methods and a general approach to coding. At work, in the grammatical analysis of the word, first of all, it is necessary to separate the base of the word and the suffix part from the word form. After that, it consists of dividing the adverbs into parts and determining the appropriate category based on the word and performing the analysis of the adverbs. Based on the developed algorithm, it can be used for grammatical analysis of not only words, but also texts. This is also important in corpus linguistics.